Studi Komunikasi Instruksional dalam Metode Phonics di Lezaleza English Course Bandung - Hana Rengganawati (Program Studi Hubungan Masyarakat Politeknik LP3I, 2021)
ABSTRACT This study aims to determine how the instructional communication with Phonics method in Lezaleza English Course Bandung is implemented. This research is descriptive and qualitative. The components are five instructional communication processes including the process of content specification and instructional objectives. First, the teacher creates a special Lesson-Plan through LezaLeza Text-Book, Exercise-Book and Blending Table. Second, the initial behavior assessment, Teacher always asks questions and repeats material to analyze students' abilities. Third, Determination of instructional strategies, the Teacher uses the Method of Storytelling, Question and Answer, Singing, and Playing Games. Fourth, Instructional unit organization, Teacher arranges material gradually starting from recognizing the alphabet's sound to making word pronunciation. Fifth, feedback, students' responses are verbal and nonverbal. The results were positive responses, easier English, active and communication is dialogic. The positive response also shown by parents who were satisfied and assured of their child's education. Keywords: Instructional Communication, Phonics Method, English ABSTRAK Penelitian ini bertujuan untuk mengetahui bagaimana komunikasi instruksional dalam metode Phonics di Lezaleza English Course Bandung diimplementasikan. Penelitian ini adalah deskriptif kualitatif. Komponen yang terlibat adalah lima proses komunikasi instruksional yang meliputi proses spesifikasi isi dan tujuan instruksional. Pertama, pengajar membuat Lesson Plan khusus melalui LezaLeza Text Book, Exercise Book dan Blending Table.. Kedua, penaksiran perilaku mula, pengajar selalu bertanya dan mengulang materi untuk menganalisa kemampuan muridnya. Ketiga, penetapan strategi instruksional, pengajar menggunakan Metode Bercerita, Tanya Jawab, Bernyanyi, dan Bermain. Keempat, organisasi satuan-satuan instruksional, pengajar menyusun materi secara bertahap mulai dari pengenalan bunyi alfabet sampai dengan membuat pelafalan kata. Kelima, umpan balik, respon para murid berupa verbal dan nonverbal. Hasilnya adalah mempermudah pemahaman murid, murid lebih aktif dan komunikasi lebih dialogis. Selain itu, hasil positifnya juga diperlihatkan oleh orang tua murid yang merasa puas dan terjamin akan pendidikan anaknya. Kata kunci: Komunikasi Intruksional, Metode Phonics, bahasa Inggris